The phenology of gross ecosystem production in a macroalga and seagrass canopy is driven by seasonal temperature. Issue 4 (27th July 2020) - Hinode, Kenjiro; Punchai, Peeraporn; Saitsu, Mako; Nishihara, Gregory N.; Inoue, Yukio; Terada, Ryuta
SUMMARY: Global changes in climatic conditions are expected to disrupt marine ecosystems. Ocean warming is one of many concerns, since more than 90% of the Earth's warming occurs in the oceans. Macrophyte‐dominated communities recently have become the focus of climate mitigation due to their high carbon sequestration rate. Therefore, there is an urgent need to understand the effects of environmental variables on the phenological response of photosynthesis in entire macrophyte communities (i.e., community production). We conducted 30 monitoring surveys from May 2015 to February 2017 and collected time‐series data of environmental variables in Zostera marina (3 m depth) and Sargassum siliquastrum (1 m depth) communities. The community production and respiration from two different macrophyte communities were calculated from dissolved oxygen time‐series. Analysis of the time‐series indicated strong diurnal frequencies for dissolved oxygen, light, and net ecosystem production, whereas weekly frequencies dominated for water temperature, chlorophyll a fluorescence, and current speed. Water temperature appeared to drive mean gross ecosystem production over the course of a year and light induced variations in the short‐term and were similar in both macrophyte communities.